Spectrum of Benign Breast Diseases in Females- a 10 years study - Ahmed, Shakera; Awal, Anisul (Medicine Today, 2018)
The study was conducted to determine the frequency of various benign breast diseases in female patients, to analyze the percentage of incidence of benign breast diseases, the age distribution and their different mode of presentation. This is a prospective cohort study of all female patients visiting a female surgeon with benign breast problems. The study was conducted at Chittagong Metropolitn Hospital and CSCR hospital in Chittagong over a period of 10 years starting from July 2007 to June 2017. All female patients visiting with breast problems were included in the study. Patients with obvious clinical features of malignancy or those who on work up were diagnosed as carcinoma were excluded from the study. The findings were tabulated in excel sheet and analyzed for the frequency of each lesion, their distribution in various age group. Medicine Today 2018 Vol.30(1): 16-18